Gastrointestinal system lesions in children due to the ingestion of alkali and acid corrosive substances - Demiroren, Kaan; Kocamaz, Halil; Dogan, Yasar (Tubitak Scientific & Technological Research Council Turkey, 2015)
Background/aim: To examine esophageal and gastric lesions in children due to the ingestion of alkali and acid corrosive substances and to emphasize all related complications. Materials and methods: The reports of 103 children who ingested or were suspected to have ingested corrosive substances and who then underwent upper gastrointestinal endoscopic inspections were evaluated retrospectively. Results: Of the patients, the mean age was 41 +/- 3.6 months, and 57.3% were male. Vomiting was the most common symptom (44.7%). Eighteen different commercial products were defined as corrosive substances: 59.2% of them were alkali, 39.8% were acids, and 1% had a neutral pH. These corrosive agents most frequently contained sodium hydroxide, followed by hydrochloric acid, sodium hypochlorite, and sulfuric acid. Endoscopic inspections were abnormal in 68% of the cases. Esophageal lesions were observed in 56.3% of the patients, while gastric lesions were observed in 35%. During the follow-up period, esophageal strictures developed in 4.9% of patients, while gastric outlet obstructions developed in 1%. Conclusion: Of the patients, the mean age was 41 +/- 3.6 months, and 57.3% were male. Vomiting was the most common symptom (44.7%). Eighteen different commercial products were defined as corrosive substances: 59.2% of them were alkali, 39.8% were acids, and 1% had a neutral pH. These corrosive agents most frequently contained sodium hydroxide, followed by hydrochloric acid, sodium hypochlorite, and sulfuric acid. Endoscopic inspections were abnormal in 68% of the cases. Esophageal lesions were observed in 56.3% of the patients, while gastric lesions were observed in 35%. During the follow-up period, esophageal strictures developed in 4.9% of patients, while gastric outlet obstructions developed in 1%.
Keywords: Corrosive substance; endoscopic inspection; esophageal stricture; gastric outlet obstruction